Service-oriented design of environmental information systems - Usländer, Thomas (Karlsruher Schriften zur Anthropomatik / Lehrstuhl für Interaktive Echtzeitsysteme, Universität Karlsruhe (TH) ; Fraunhofer-Institut für Optronik, Systemtechnik und Bildauswertung IOSB Karlsruhe, 2010)
Service-orientation has an increasing impact upon the design process and the architecture of environmental information systems. This thesis specifies the SERVUS design methodology for geospatial applications based upon standards of the Open Geospatial Consortium. SERVUS guides the system architect to rephrase use case requirements as a network of semantically-annotated requested resources and to iteratively match them with offered resources that mirror the capabilities of existing services.